Molecular Testing for COVID-19: What the Clinician Should Know - Nermin Kamal Saeed; Mohammed Al-Biltagi; Adel Salah Bediwy (Dr. Sulaiman Al Habib Medical Journal)
Coronavirus Disease 2019 (COVID-19) is a major challenge for health systems worldwide. Molecular diagnosis is a cornerstone in the management of COVID-19. Clinicians should understand the various aspects of molecular testing that may influence their judgment and management. Cycle threshold, viral shedding, and recurrence are among the most common areas of conflict among clinicians. In this review, we discuss these areas of conflict from a clinical perspective.